2021
DOI: 10.1177/23992026211008805
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to prenatal iron–folic acid supplementation and associated factors among pregnant women attending antenatal care services in Dilla town, South Ethiopia

Abstract: Background: During pregnancy, due to the physiological and hormonal change, the requirement of iron–folic acid is enhanced. Therefore, the occurrence of iron/folic acid deficiency is relatively high and it is responsible for 95% of anemia during pregnancy. Objectives: The aim of this study was to assess adherence to prenatal iron–folic acid supplementation (IFAS) and associated factors among pregnant women attending antenatal care services at public health facilities of Dilla town. Methods: Facility-based cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…In this study, the overall compliance rate of iron supplementation during pregnancy was found to be 92.4%. The current finding was higher than many previous reports in Ethiopia, such as the compliance rate, which varied from 60 to 63.6% in Addis Ababa 32 , 44 , 45 , 87.6% in Ethiopia 37 , Dire Dawa 46 , Shalla District 47 , 43.4% Dilla town 48 , 38.3% Hadassah 28 , 51.4% Burin district 49 , 52.9% Debbie 50 , 28.1% Denbiya District 36 , 28.7% Lay Armachiho 31 , 55% Gondar 51 , 47.6% Aykal town 30 , 44% Debre Tabor 52 , 43% Wollo 53 and 74.9% in four regions of Ethiopia 20 , 67.6% Simada district 54 , 52.8% Debay Tilat Gen district 55 , 37.2% Northwestern zone of Ethiopia 35 , 55.5% Debre Markos town 56 , 76.9% Dangila, Northern Ethiopia 57 , 40.9% in Adwa town 58 , and meta-analyses, 46.15, 46.1, 41.38 and 43.63% 59 62 . The present finding was also higher than many others, for example, a meta-analysis in SSA 63 , Uganda 64 , Kenya 65 , Nigeria 24 , Northwest Tanzania 66 , Northern Tanzania 67 , 22 sub-Saharan African countries 23 , Niger 68 , West Iran 69 , Cambodia 34 , Nepal 70 , 71 , India 72 , and Sri Lanka 73 .…”
Section: Discussioncontrasting
confidence: 85%
“…In this study, the overall compliance rate of iron supplementation during pregnancy was found to be 92.4%. The current finding was higher than many previous reports in Ethiopia, such as the compliance rate, which varied from 60 to 63.6% in Addis Ababa 32 , 44 , 45 , 87.6% in Ethiopia 37 , Dire Dawa 46 , Shalla District 47 , 43.4% Dilla town 48 , 38.3% Hadassah 28 , 51.4% Burin district 49 , 52.9% Debbie 50 , 28.1% Denbiya District 36 , 28.7% Lay Armachiho 31 , 55% Gondar 51 , 47.6% Aykal town 30 , 44% Debre Tabor 52 , 43% Wollo 53 and 74.9% in four regions of Ethiopia 20 , 67.6% Simada district 54 , 52.8% Debay Tilat Gen district 55 , 37.2% Northwestern zone of Ethiopia 35 , 55.5% Debre Markos town 56 , 76.9% Dangila, Northern Ethiopia 57 , 40.9% in Adwa town 58 , and meta-analyses, 46.15, 46.1, 41.38 and 43.63% 59 62 . The present finding was also higher than many others, for example, a meta-analysis in SSA 63 , Uganda 64 , Kenya 65 , Nigeria 24 , Northwest Tanzania 66 , Northern Tanzania 67 , 22 sub-Saharan African countries 23 , Niger 68 , West Iran 69 , Cambodia 34 , Nepal 70 , 71 , India 72 , and Sri Lanka 73 .…”
Section: Discussioncontrasting
confidence: 85%
“…11 The adherence rate in similar study contexts was reported to be 43.4% and 38.3% in Ethiopian institution-based crosssectional research. 15,16 Differences in lifestyle, pregnant women's understanding of IFAS, and respondents' educational status could be contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the effect of anemia knowledge and iron tablet supplementation on pregnant women's adherence to consuming iron tablets was obtained from the ten articles reviewed. Eight articles stated that knowledge about anemia and iron tablet supplementation was one of the significant factors related to adherence [6,9,12,14,[16][17][18][19], while the other two articles did not find a significant association between knowledge and the adherence of pregnant women to consuming iron tablets [10,17].…”
Section: The Effect Of Knowledge On Adherencementioning
confidence: 99%
“…Anemia knowledge questionnaire items include signs and symptoms of anemia, risk factors, causes, consequences of anemia on the mother and fetus, and knowing how to prevent and treat anemia. After carrying out a binary multivariate logistic test, it was found that mothers who had good knowledge about anemia were 2-5 times more likely to comply than mothers who had poor knowledge [6,9,11,14,16,19]. Knowledge of iron tablet supplementation increases the chances of adherence 2-3 times.…”
Section: The Effect Of Knowledge On Adherencementioning
confidence: 99%